2009
DOI: 10.1063/1.3190537
|View full text |Cite
|
Sign up to set email alerts
|

Experimental scaling law for mass ablation rate from a Sn plasma generated by a 1064 nm laser

Abstract: The ablation depth in planar Sn targets irradiated with a pulsed 1064 nm laser was investigated over laser intensities from 3×1011 to 2×1012 W/cm2. The ablation depth was measured by irradiating a thin layer of Sn evaporated onto a Si wafer, and looking for signatures of Si ions in the expanding plasma with spectroscopic and particle diagnostics. It was found that ablation depth scales with laser intensity to the (5/9)th power, which is consistent with analytical models of steady-state laser ablation, as well … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 52 publications
(32 citation statements)
references
References 17 publications
2
29
0
1
Order By: Relevance
“…Since the second heating pulse does not contribute to further sample removal, one is able to quantitatively compare SP-and DP-LIBS results using the same amount of ablated mass and demonstrate the improvement in excitation provided by DP-LIBS. Burdt et al [30] have shown through experiments, modeling, and comparisons to similar works that proved consistent to theirs, that the mass ablation rate is proportional to laser intensity as ṁ ∝ I L 5/9 for constant laser wavelength and target. As laser intensity is directly proportional to laser energy, the mass ablation rate can be rewritten as ṁ ∝ E L 5/9 to compare the sample removal rates at different prepulse laser energies.…”
Section: Double Pulse Libssupporting
confidence: 58%
“…Since the second heating pulse does not contribute to further sample removal, one is able to quantitatively compare SP-and DP-LIBS results using the same amount of ablated mass and demonstrate the improvement in excitation provided by DP-LIBS. Burdt et al [30] have shown through experiments, modeling, and comparisons to similar works that proved consistent to theirs, that the mass ablation rate is proportional to laser intensity as ṁ ∝ I L 5/9 for constant laser wavelength and target. As laser intensity is directly proportional to laser energy, the mass ablation rate can be rewritten as ṁ ∝ E L 5/9 to compare the sample removal rates at different prepulse laser energies.…”
Section: Double Pulse Libssupporting
confidence: 58%
“…Complete recombination is prevented by fast plasma expansion to a sufficiently rarefied state where recombination processes become negligible. 5 The EUV radiation emitted by the plasma is collected and focused with a large and expensive x-ray optic surrounding the plasma. 1,4 Charge state freezing in laser produced plasma ͑LPP͒ has important implications for several applications.…”
Section: Recombination Effects During Expansion Into Vacuum In Laser mentioning
confidence: 99%
“…1. 16,17 The charge state resolved ion energy distributions are measured with an electrostatic deflection probe and single channel electron multiplier ͑CEM͒. The experiments are conducted in vacuum below 3 ϫ 10 −6 torr so chargeexchange with the ambient will be negligible.…”
Section: Experimental Conditions and Resultsmentioning
confidence: 99%